Determinants of Internationalization: Early-stage Entrepreneurs from Southeast Europe - Leković, Bojan; Amidžić, Renata; Milićević, Nikola (Industrija, 2018)
Research area of this study includes determinants that have an influence on international ventures of early-stage entrepreneurs, nascent and new business owners. The research implies determinants such as: entrepreneurial motivation, innovation activity, use of new technology and demographic factors - gender and age. Data for the research was provided by the Global Entrepreneurship Monitor database; the sample covers data of early-stage entrepreneurs who settled their business in Southeast Europe. The methodology of empirical research provides a presentation of statistical research by using Probit regression and concept of marginal effects. According to the aim of this paper, the model was created by setting the determinants that influenced the internationalization activity. The research results show that increase-wealth opportunity motivated early-stage entrepreneurs, internationalize more than the necessity entrepreneurs or early-stage entrepreneurs driven by the motive of independence. Early-stage entrepreneurs, who use new technology and prefer radical innovations, are more oriented on foreign markets and customers. Also, there is a significant influence of demographic factors such as entrepreneurial gender and age on internationalization activity. Analysis of entrepreneur’s internationalization at the country level shows the differences between the countries of Southeast Europe.
Keywords: Innovation; Southeast Europe; Technologies; Motivation; Internationalization; Entrepreneurship